Analisis Penggunaan Media Kartu Huruf dalam Meningkatkan Kemampuan Membaca Siswa Kelas 1 SD Negeri Cengkareng Barat 14 Pagi - Gumilar, Aris; Mutaqijn, Imam; Yuliyanti, Ike (TSAQOFAH, 2022)
This research is motivated by the results of a preliminary study conducted by researchers in the field showing that students' interest in reading is very lacking, especially regarding good reading comprehension, causing elementary school students who are at the concrete stage to need tools in the form of media that can clarify what will be conveyed by the teacher. This study uses a qualitative approach. The instruments used are student observations, reading skills, interviews and assignments. Based on the results of the study, several research findings were obtained through data collection tools such as observation, interviews, and documentation. In the research on Analysis of Using Letter Card Media in Improving Reading Ability for Grade 1 SD Negeri Cengkareng Barat 14 Pagi, the findings of this study will be analyzed for data including data reduction, data presentation, and drawing conclusions. Based on the results of the research and discussion that have been described, it can be concluded as follows. After the implementation of letter card media in learning to read the beginning of grade 1 SD Negeri Cengkareng Barat 14 Pagi there was an increase of 81.25%. Thus, the application of letter card media can improve the early reading ability of students in grade 1 SD Negeri Cengkareng Barat 14 Pagi in 2021/2022.